(untitled) (Global Journal of Management and Business Research, 2014)
This paper explores the impact of church marketing and its effect on church attendance growth. Evidence was gathered from the analysis of a randomly-drawn sample size of 132 which involves 12 pastors, and 120 members from six charismatic churches. Results from the calculated Pearson correlation indicates that positive relationship exist between ’church promotion’ and church attendance growth although regression results show that among all the variables considered in the study, it is ’Radio PR’ that plays a major role in influencing the growth of churches in Ghana. The study concludes that ’Radio PR tool’ has been the most effective tool influencing church attendance growth in Ghana.